Psychological Factors for The Formation Of Bilinguals In Preschool Children - Pulatova Gulnoza Murodilovna. (Euro Asian Journal Publishing, 2024)
in childhood, bilingualism (bilingualism) is formed in the life of a child, instead of the capture of each language, depending on what situations and to what extent he uses bilingualism.The article presents the concept of bilingualism and the specific psychological characteristics of the formation of bilingualism in preschool age,factors of formation
Keywords: language; bilingualism; Psycholinguistics; genetics